Konsep Perceraian Suku Lani, Kabupaten Lanny Jaya Distrik Karu, Papua Ditinjau Dari Sudut Pandang Matius 19:1-12 dan Dampaknya bagi Pendidikan Anak dalam Keluarga Kristen - Baskoro, Paulus Kunto; Yikwa, Abius (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2024)
Divorce is a problem that often occurs in the lives of Christians today. God himself hates divorce (Mal.2:16) because God unites man and woman into one flesh. Men and women as husband and wife are united in marriage (Gen. 2:24). But in reality, divorce occurs everywhere in the lives of Christians today. This research will focus on how to study divorce according to Matthew 19:1-12, which is viewed from the divorce incident that occurred in the Lani tribe, Papua. Especially in Papua, divorce cases tend to increase and their impact on children's education. Papuans with their different ethnic, cultural, linguistic and religious backgrounds are not free from the problem of divorce in the family. Divorce is carried out according to the culture of each tribe in Papua. According to the Central Statistics Agency (BPS) 2021, the highest divorce rate in Papua was recorded in the city of Sorong at 0.85% in 2021. Furthermore, in other districts in Papua there were divorces between Christians in the household. The method used is a descriptive qualitative method. The aim of this research is First, the important role of husband and wife in maintaining the quality of marriage. Second, the church is an important part of maintaining the integrity of marriage in the Lani tribe. Third, building a strong family for children's education in the family.AbstrakPerceraian merupakan masalah yang sering terjadi dalam kehidupan orang Kristen pada masa kini. Tuhan sendiri membenci perceraian (Mal.2:16) karena Tuhan mempersatukan laki-laki dan perempuan menjadi satu daging. Laki-laki dan perempuan sebagai suami istri satu ikatan dalam pernikahan (Kej. 2:24) Tetapi pada kenyataannya perceraian terjadi dimana-mana dalam kehidupan orang Kristen pada masa kini. Penelitian ini akan fokus bagaimana mengkaji perceraian menurut Matius 19:1-12, yang ditinjau dari peristiwa perceraian yang terjadi di suku Lani, Papua. Khususnya di Papua kasus perceraian cenderung meningkat dan dampaknya bagi pendidikan anak. Papua dengan latar belakang suku, budaya, bahasa dan agama yang berbeda-beda tidak terlepas dari masalah perceraian dalam keluarga. Perceraian dilakukan menurut budaya di suku masing-masing yang ada di Papua. Menurut Badan Pusat Statitik (BPS) 2021 angka perceraian yang paling tinggi di Papua tercatat di kota Sorong 0,85% pada tahun 2021. Selanjutnya kabupaten lain di Papua terjadi perceraian terhadap orang Kristen di dalam rumah tangga. Metode yang digunakan adalah metode kualitatif deskritif. Tujuan dari penelitian ini adalah Pertama, peran penting suami isteri menjaga kualitas pernikahan. Kedua, gereja menjadi bagian penting menjaga keutuhan pernikahan di suku Lani. Ketiga, membangun keluarga yang kuat bagi pendidikan anak dalam keluarga Kristen.